Co-regulating the surface and bulk structure of Li-rich layered oxides by a phosphor doping strategy for high-energy Li-ion batteries. Issue 14 (18th March 2019) - Wang, Min-Jun; Yu, Fu-Da; Sun, Gang; Wang, Jian; Zhou, Ji-Gang; Gu, Da-Ming; Wang, Zhen-Bo
Abstract : A novel phosphor doping strategy renders commendable homogeneity in the chemical environment and phase distribution between the surface and bulk of Li-rich materials. Abstract : Li-rich layered materials, despite their high specific capacity up to 250 mA h g −1, suffer from structural transformation either in the initial activation or after cycling, causing continuous voltage decay and capacity fading. Anion doping has been widely considered as a way to stabilize the intrinsic structure and improve the electrochemical performance of Li-rich materials, though with the pain of process complexity and limitation. Here, we report a simple co-precipitation method with a dual sedimentating agent to realize phosphor doping in both the surface and bulk. X-ray diffraction Rietveld refinement results indicate that the doped sample presents a larger lattice spacing than the normal sample and a Li3 PO4 protective layer in situ forms on the surface. Synchrotron scanning transmission X-ray microscopy (STXM) reveals commendable homogeneity in the phase distribution between the surface and bulk in the doped sample. X-ray absorption near edge structure (XANES) shows a more homogeneous local chemical environment of the doped sample by investigating the Mn, Ni, and Co L-edges and O K-edge spectra. The doped sample displays a high discharge capacity of 295 mA h g −1 with an initial coulombic efficiency of 90.5% at 0.1C, showing a high rate performance of 247 mA h g −1 at 1C and a superior capacity retention of 73% after 500 cycles. Moreover, this doping strategy also inhibits the critical voltage decay of Li-rich materials during cycling. The prolonged structural evolution analysis demonstrates that phosphor doping can play a stabilizing role in Li-rich materials to restrain the transformation from layer to spinel.